Reframing Tentmaking Ministry: A Theological–Ethical Critique of Contemporary Practice in South Africa - Thinane, Jonas Sello (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2025)
“Tentmaking ministry” has become a common term in contemporary church discourse to legitimise dual engagement in secular employment and pastoral service. Yet the concept often lacks precision and has generated ethical contestation, especially in church contexts marked by economic precarity and the increasing commercialisation of religion. This article offers a conceptual and theological-ethical critique of contemporary tentmaking ministry in South Africa. Rather than presenting new empirical data, it develops an analytical framework by reconstructing a Pauline normative baseline from key texts in Acts and the Pauline epistles (Acts 18:3; 1 Thess 2:9; 1 Cor 9:15; Acts 20:33–35) and placing that baseline in critical dialogue with scholarship on bi-vocational ministry and the political economy of religion. The analysis argues that when “tentmaking” functions primarily as income supplementation alongside sustained church remuneration, it increasingly resembles moonlighting rather than Pauline self-support. This shift raises concerns about ministerial accountability, the moral economy of church resources, and the long-term sustainability of congregational life. The article contributes (i) a clarified typology distinguishing Pauline tentmaking, bi-vocational ministry, moonlighting, and full-time ministry and (ii) a set of normative criteria for discerning authentic tentmaking in the twenty-first century, including motivational orientation, transparency, proportionality, time accountability, protection of the poor and mission-critical resources, contextual sensitivity, and periodic review. By reframing tentmaking as an ethically structured practice rather than a flexible label for dual employment, the study provides churches and denominational bodies with constructive guidance for evaluating economic arrangements in ministry, while safeguarding mission integrity and communal responsibility.